2020
DOI: 10.4103/jehp.jehp_564_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of life skills health education program: A quasi-experimental study among school students of South India

Abstract: BACKGROUND: Adolescence is a vital stage of growth and development; however, many adolescents do die prematurely due to accidents, suicide, violence, poor mental stability, depression, and other illnesses that are either preventable or treatable. Life skills are important for the promotion of well-being of adolescents and to develop positive attitude and values to lead a healthy life. OBJECTIVES: The study was conducted to assess the change in life skills postinterventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Decision making, problem solving, communication skills, interpersonal relationship skills, coping with emotions, coping with stress, creative thinking and critical thinking were increased post-training, as proven previously by different studies on school students [ 31 ]. The fact that the LSTCP training was conducted in groups of 25 participants and was delivered through an experiential learning process resulted in better involvement and interaction between facilitators and participants.…”
Section: Discussionsupporting
confidence: 66%
“…Decision making, problem solving, communication skills, interpersonal relationship skills, coping with emotions, coping with stress, creative thinking and critical thinking were increased post-training, as proven previously by different studies on school students [ 31 ]. The fact that the LSTCP training was conducted in groups of 25 participants and was delivered through an experiential learning process resulted in better involvement and interaction between facilitators and participants.…”
Section: Discussionsupporting
confidence: 66%
“…Low family participation conditions the results [29]. When there is involvement and commitment on the part of families in the development of the programs, achievement of the results and goals of the program is favored [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The development of this type of program favored peer training, as well as the development of creative, critical, interpersonal thinking, and self-awareness skills that are fundamental for life [25]. Students learn in this way and by putting these skills into practice, to face health-related problems responsibly [31]. Peer learning has been established as a basic strategy for the promotion and consolidation of healthy habits and behaviors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Life skills training has also been found to be effective in reducing suicidal tendencies among individuals (Refahi, 2008;LaFromboise & Hayes, 2008;Wyman, 2014;Fekkes et al, 2016;Ram et al, 2020) (Fekkes et al, 2016;Ram, Koneru, & Gowdappa, 2020;Refahi, 2008;Wyman, 2014). Further, life skills training was found to have significant impact on individuals' health-related behaviour (Botvin & Griffin, 2002;Gupta et al, 2014;Sahebalzamani, Moraveji, Farahani, & Feizi, 2013;Tiwari, Naik, Nirgude, & Dutta, 2020). Likewise, it is suggested that intervention efforts for adolescent emotional reactions and suicidal behaviour need to be appropriate to the developmental level (Barkhordar et al, 2016;Gupta et al, 2014;Jamali et al, 2016;Mohammadi & Nejad, 2014).…”
Section: Review Of Related Literaturementioning
confidence: 99%